2016
DOI: 10.1007/s12199-016-0534-2
|View full text |Cite
|
Sign up to set email alerts
|

Association of perfluorinated chemical exposure in utero with maternal and infant thyroid hormone levels in the Sapporo cohort of Hokkaido Study on the Environment and Children’s Health

Abstract: These findings suggest that PFOS may independently affect the secretion and balances of maternal and infant TSH even at low levels of environmental exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 41 publications
1
51
0
Order By: Relevance
“…In humans, however, the situation is less clear. For the compounds considered in the present study, some studies have reported negative associations with T 4 levels in blood (DH Makey et al 2016;Zheng et al 2017;Zota et al 2011), but other studies have reported positive associations (EFSA 2011a;Shrestha et al 2017;Stapleton et al 2011), concentration-dependent associations (Zhao et al 2015), or a lack of associations (Audet-Delage et al 2013;Kato et al 2016;Olsen et al 2003). The observed difference between rodent and human studies is attributed to the fact that humans have a reserve of T 4 stably bound to TBG.…”
Section: Discussionmentioning
confidence: 60%
“…In humans, however, the situation is less clear. For the compounds considered in the present study, some studies have reported negative associations with T 4 levels in blood (DH Makey et al 2016;Zheng et al 2017;Zota et al 2011), but other studies have reported positive associations (EFSA 2011a;Shrestha et al 2017;Stapleton et al 2011), concentration-dependent associations (Zhao et al 2015), or a lack of associations (Audet-Delage et al 2013;Kato et al 2016;Olsen et al 2003). The observed difference between rodent and human studies is attributed to the fact that humans have a reserve of T 4 stably bound to TBG.…”
Section: Discussionmentioning
confidence: 60%
“…Some studies also reported similar inconsistent observations224041). In Hokkaido cohort with matched mother and child pairs (n=39), PFOS levels measured in 24 weeks of pregnancy showed a negative association with maternal TSH, but a positive association with cord serum TSH.…”
Section: Pfass Exposure and Thyroid Hormone Disruption In Susceptiblementioning
confidence: 81%
“…Several important potential covariates, including smoking, fish intake and environmental contaminants such as PFOS and mercury were considered. Our previous reports on the same cohort showed that PFOA, Mono-2-ethylhexyl phthalate, Bisphenol A are not associated with maternal or neonatal TH levels (Kato et al, 2016;Minatoya et al, 2016;Minatoya et al, 2017).…”
Section: Strengths and Limitationsmentioning
confidence: 88%
“…The models were adjusted for variables that were significantly associated with TSH or FT4 levels at p < 0.05 level in the univariate analysis (data not shown). PFOS was included in the model for maternal THs becauseKato et al (2016) previously reported that, in multivariate analyses, PFOS were significantly associated with maternal TSH in the same cohort. Mercury was associated with total TEQ/PCBs, but not with THs, therefore it was not adjusted for in the multivariate model.…”
mentioning
confidence: 99%